Peningkatan Kemandirian Belajar dan Minat Belajar Mahasiswa Mata Kuliah Elektronika Analog dengan Pembelajaran PBL - Suparman Suparman (Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
The objective of the study was to improve the students’ interest and learning independence through Problem Based Learning (PBL) in the course of Analog Electronics. This study was categorised into classroom action research. It was conducted in two cycles, each cycle consisted of two meetings. The results revealed the following: (1) the mean scores of the students’ learning independence in the first and the second cycle were 2.9756 and 8.1951 respectively, thus it proved that the implementation of PBL in the course of Analog Electronics  improved the students’ learning independence; (2) the mean scores of the students’ interest in the first and the second cycle were 2.2927 and 5.8536 respectively, thus it indicated that the implementation of PBL in the course of Analogue Electronics improved the students’ interest.